Componentes carcaça e não carcaça de cordeiros Santa Inês submetidos à restrição alimentar - Santos, Adrielle Albuquerque dos (2014)
The present study was conducted to investigate the effect of sex class(castrated and non- castrated) and levels of feed restriction (0%, 30% e 60%) on the quantitative characteristics of carcass and non-carcass components of Santa Ines lambs. We used thirty Santa Ines lambs, castrated (n=15) and non–castrated (n=15) with approximately two months of age and average initial body weight of 13 ± 1.49 kg. The lambs were assigned to a completely randomized design in a 3x2 factorial arrangement (restriction level x sex class), according to the amount of food provided (0%, 30% and 60% restriction). Experiment period was determined based in the time required for the animals of one of the groups achieved 28 kg of average body weight, when all 30 animals were slaughtered. We found the influence of sex class on quantitative traits body weight at slaughter, empty body weight, hot and cold carcass weight non castrated animals showed higher averages than the castrated animals. The weight of the leg of the non- castred animal (1,727) was biggest than the castrated animals (1,637). Was observed interaction between sex class and dietary restriction for the all of characteristics of carcass, except to leg yield and back rib. Interaction between restriction levels and genders was not observed for non-carcass components. There were differences between genders for the weights of the kidneys, paws, blood and large intestine of non-castrated animals, which had higher averages than castrated animals. A linear decreasing effect to the restriction levels were observed for blood, head, skin, paw, rumen-reticulum, abomasum, small intestine, large intestine and perirenal fat, omental fat, mesenteric and heart fats. Quantitative characteristics of carcass and non-carcass components of growing Santa Ines lambs are influenced by sex class and dietary restriction levels.